Impact of Globalization on Purchasing and Procurement in Jordan - Allah, Aabidah (Global Journal of Purchasing and Procurement Management, 2023)
Purpose: The study sought to analyze the impact of globalization on purchasing and procurement in Jordan. Methodology: The research was conducted entirely on computers. Secondary data, or data that doesn't require actual observation in the field, are the focus of desk research. Because it requires little more than an executive's time, telephone rates, and directories, desk research is generally seen as a low-cost strategy in comparison to field research. As a result, the research used data that had already been collected and reported. This secondary data was readily available via the internet's digital library and scholarly articles. Findings: The results show that globalization has had a major impact on purchasing and procurement, creating both opportunities and challenges. The procurement process has become more complex, with a greater focus on collaboration and long-term relationships with suppliers. Organizations must be prepared to adapt to these changes in order to remain competitive in a globalized world. In Jordan in Jordan, the country's access to global markets, foreign investment, and technological advances have helped to integrate the country into the global economy. Unique Contribution to Theory, Practice and Policy: Future research in the field of purchasing and procurement may be grounded in the global value chain theory and the transaction cost economics theory. Policymakers, researchers and academics from all across the world will all stand to gain from this study's findings. Executives in charge of national purchasing and procurement initiatives will also use the study's findings to boost the urbanization performance across the board. The research suggests that the purchasing and procurement sector should implement globalization policies to boost the effectiveness of their primary operations and activities.